Morphological testicular changes following the experimental inguinal hernia repair modeling - N. G. Kulchenko (Исследования и практика в медицине, 2021)
Purpose of the study. To evaluate morphological changes in the testes in experimental animals after tension-free inguinal hernia repair modeling.Materials and methods. The study included male rabbits, aged 120 days, weighing 3.8 ± 0.9 kg. All rabbits were divided into two groups depending on the type of operation: in the first group (n = 10) of animals, we made a model of tension-free inguinal hernia repair and used a polypropylene mesh; in the second group (n = 10) of animals, we left the structures of the inguinal canal intact. Morphological assessment of spermatogenesis was performed after 40 days. All morphometric measurements were carried out on strictly cross-sections of the convoluted seminal tubules.Results. In rabbits of group 1, the volume of the testicle was significantly three times less than in animals of group 2 (p < 0.05). In the animals of the first group, a significant deterioration in spermatogenesis was observed (p < 0.05). Histological examination of sections of the testes of these animals showed that hypoplasia of the spermatogenic epithelium was present in the convoluted seminal tubules, in 1/8 of the tubules there was subtotal aplasia of the spermatogenic epithelium, Sertoli-Cell-Only Syndrome was detected only in 2 %. Atrophy of the convoluted seminal tubules was not recorded at this period of observation. In the animals of the control group, almost 90 % of cases of spermatogenesis disorders were not detected.Conclusions. This experimental study on rabbits showed that after using a polypropylene mesh for inguinal canal plastic, inhibition of germ cell maturation occurs after 1.5 months. Therefore, in men of reproductive age, it is necessary to use polypropylene mesh implants with caution in terms of performing inguinal hernia repair.